Composite conductive paper and preparation method thereof

By dispersing nanomaterials such as titanium dioxide and graphene in polyimide-based conductive paper, composite conductive paper with excellent mechanical properties and electrical conductivity was prepared, which solved the application problem of conductive paper in high temperature environments and achieved both conductivity and mechanical properties.

CN119736818APending Publication Date: 2025-04-01JILIN GAOQI JUXIANYAAN MATERIAL CO LTD +1
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411904020.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-23
Publication Date
2025-04-01

AI Technical Summary

Technical Problem

The application of polyimide-based conductive paper at low and high temperatures is limited, and the prior art is difficult to improve conductivity and conductivity uniformity without reducing mechanical properties.

Method used

By dissolving diamine in an organic solvent, titanium dioxide and graphene for ultrasonic dispersion treatment, and then adding dianhydride for polycondensation reaction, a mixture of polyamic acid, titanium dioxide and graphene was obtained, and composite conductive paper with a multi-layer structure was prepared by wet spinning and dispersion treatment of coating liquid.

Benefits of technology

It realizes the excellent mechanical properties, conductivity, conductivity uniformity and long-term high temperature resistance of composite conductive paper, and is suitable for the fields of conductivity, infrared emission and electromagnetic shielding.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119736818A_ABST
    Figure CN119736818A_ABST
Patent Text Reader

Abstract

The present invention relates to composite conductive paper and a preparation method thereof, the method comprising: (1) dissolving a diamine in an organic solvent, then adding titanium dioxide and graphene and performing ultrasonic dispersion treatment, then adding dianhydride for polycondensation reaction, then degassing to obtain a mixture, and dividing the mixture into a first mixture and a second mixture; (2a) wet spinning, wet papermaking, drying and imidization treatment of the first mixture to obtain a polyimide-based composite fiber paper, which is used as a substrate paper; (2b) adding a solution containing an organic solvent and a dispersant to the second mixture, then mixing to obtain a coating stock solution; then adding carbon nanotubes to the coating stock solution, and performing dispersion treatment to obtain a coating liquid; (3) coating the coating liquid on the substrate paper, performing thermal imidization treatment, and then pressing to obtain the composite conductive paper. The composite conductive paper has excellent mechanical properties, conductive properties, conductive uniformity and long-term high temperature resistance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the field of polyimide-based conductive paper, and in particular to a composite conductive paper comprising polyimide, titanium dioxide, graphene and carbon nanotubes and a preparation method thereof. Background Art

[0002] Conductive paper is a kind of functional paper with conductivity, which is widely used in communication products, medical instruments, home appliances and aerospace equipment. Polymer-based conductive paper has been widely used due to its simple molding process and corrosion resistance. In particular, aramid (aromatic polyamide) and polyimide have excellent comprehensive properties such as heat resistance and corrosion resistance, so they have been used as conductive paper substrates, and aramid-based conductive paper and polyimide-based conductive paper have been developed.

[0003] However, with the rapid development of science and technology, the application of aramid-based conductive paper at low and high temperatures has been limited.

[0004] In addition, polyimide-based fiber paper has high mechanical properties because it is mainly composed of polyimide chopped fibers. It can be used for a long time in a high temperature environment above 200°C, and its performance is better than that of aramid-based fiber paper. However, polyimide-based fiber paper is not conductive. Therefore, it is necessary to improve its conductivity without significantly reducing its mechanical properties. For example, polyimide-based fiber paper is modified by using additives such as graphene nanomaterials and carbon nanotubes to improve conductivity.

[0005] Graphene is a two-dimensional carbon nanomaterial with excellent electrical, thermal and mechanical properties. However, the disadvantage of graphene is that it easily aggregates in solution and is difficult to disperse.

[0006] Carbon nanotubes have good mechanical properties and electrical conductivity. However, the disadvantage of carbon nanotubes is that their dispersibility is worse than that of graphene. Usually, only a small amount of carbon nanotubes can be doped into polyimide-based fiber paper to improve conductivity.

[0007] In addition, for polyimide-based conductive paper formed by coating or impregnation process, because the additives used in the preparation cannot be evenly dispersed, the thickness of the paper after impregnation or coating will have obvious differences, that is, poor thickness uniformity, resulting in uneven surface resistance and poor conductivity under low voltage. In addition, defects are easily caused during the drying process after impregnation or coating, which increases the surface resistance of the defective part or even insulates it. The resistance changes greatly after long-term use, and there are also disadvantages of powder loss and detachment.

[0008] In order to make polyimide-based conductive paper widely used, it is necessary to improve the conductivity and uniformity of the paper without affecting the mechanical properties of the paper, and the mechanical properties and conductive properties should not be significantly reduced after long-term use at high temperature (above 200°C). Summary of the invention

[0009] Technical issues

[0010] An object of the present invention is to provide a method for preparing composite conductive paper, which has a simple process and can produce the composite conductive paper on a large scale.

[0011] Another object of the present invention is to provide a composite conductive paper having excellent mechanical properties (such as tensile strength), conductive properties, conductive uniformity and long-term high temperature resistance by comprising a substrate paper having a specific composition and a coating layer.

[0012] Technical Solution

[0013] According to one aspect of the present invention, there is provided a method for preparing a composite conductive paper, the method comprising the following steps:

[0014] (1) dissolving a diamine in an organic solvent, then adding titanium dioxide and graphene and performing ultrasonic dispersion treatment, then adding dianhydride to perform polycondensation reaction, and then degassing to obtain a mixture containing polyamic acid, titanium dioxide and graphene, and

[0015] dividing the mixture into two parts: a first mixture as a spinning dope, and a second mixture for coating;

[0016] (2a) subjecting the first mixture to wet spinning, wet papermaking, drying and imidization treatment to obtain a polyimide-based composite fiber paper containing titanium dioxide and graphene, which is used as a substrate paper;

[0017] (2b) adding a solution containing an organic solvent and a dispersant to the second mixture obtained in step (1), followed by mixing to obtain a coating stock solution;

[0018] Then, adding carbon nanotubes to the coating stock solution and performing a dispersion treatment to obtain a coating solution containing polyamic acid, titanium dioxide, graphene and carbon nanotubes;

[0019] (3) The coating liquid is coated on both surfaces of the substrate paper obtained in step (2a), and subjected to thermal imidization treatment, and then pressed to obtain a composite conductive paper having a multilayer structure.

[0020] In one embodiment, in step (1),

[0021] The diamine is one or more selected from 4,4'-diaminodiphenyl ether, 4,4'-diaminodiphenylmethane, 1,6-hexanediamine, triphenyl diether diamine, 2,5-bis(4-aminophenyl)pyrimidine, 5-amino-2-(4-aminophenyl)benzoxazole, and 4,4'-bis(4-aminophenoxy)biphenyl,

[0022] The organic solvent is one or more selected from N,N'-dimethylacetamide, N-methylpyrrolidone, N,N'-dimethylformamide, and dimethyl sulfoxide.

[0023] The dianhydride is one or more selected from 1,2,4,5-pyromellitic dianhydride, 3,3',4,4'-biphenyltetracarboxylic dianhydride, 3,3',4,4'-benzophenonetetracarboxylic dianhydride, 3,3',4,4'-diphenyl ether tetracarboxylic dianhydride, bisphenol A type diether dianhydride, bisphenol F type diether dianhydride,

[0024] The molar ratio of the diamine to the dianhydride is 1:0.95-1;

[0025] The added amount of the combination of the diamine and the dianhydride is 8 to 15 parts by weight relative to 100 parts by weight of the organic solvent;

[0026] The amount of titanium dioxide added is 0.5 to 6 parts by weight relative to 100 parts by weight of the organic solvent.

[0027] The added amount of the graphene is 0.5 to 6 parts by weight relative to 100 parts by weight of the organic solvent;

[0028] The weight ratio of the first mixture to the second mixture is 70-80:30-20.

[0029] In one embodiment, in step (2a),

[0030] The drying temperature is 50℃~100℃, and the drying time is 5min~40min.

[0031] The imidization is thermal imidization performed at a temperature of 200°C to 400°C.

[0032] In one embodiment, in step (2b),

[0033] The organic solvent is one or more selected from N,N'-dimethylformamide, N-methylpyrrolidone, N,N'-dimethylacetamide, and dimethyl sulfoxide.

[0034] The dispersant is one or more selected from PEG-600, polystyrene, PEG-200, PEG-400, vinyl bisstearamide, and tristearic acid glyceryl.

[0035] wherein, relative to 100 parts by weight of the second mixture, the amount of the organic solvent added is 80 to 120 parts by weight, and the amount of the dispersant added is 0.1 to 5 parts by weight,

[0036] The amount of the carbon nanotubes added is 0.1 to 10 parts by weight relative to 100 parts by weight of the coating stock solution.

[0037] In one embodiment, in step (3),

[0038] The coating amount of the coating liquid is 5 to 100 g / m 2 ,

[0039] The temperature of the thermal imidization treatment is 200-350°C.

[0040] The pressing includes soft roller pressing and hard roller pressing.

[0041] The temperature of the soft rolling is 50-200°C and the pressure is 0.1-2MPa.

[0042] The temperature of the hard rolling is 100-350° C., and the pressure is 0.1-3 MPa.

[0043] According to another aspect of the present invention, there is provided a composite conductive paper, which is prepared by the above method, wherein a coating is provided on each of the two surfaces of the substrate paper,

[0044] The substrate paper comprises polyimide fiber, titanium dioxide and graphene,

[0045] The coating comprises polyimide, titanium dioxide, graphene and carbon nanotubes.

[0046] Beneficial Effects

[0047] The method of the present invention improves the dispersibility of polyimide fiber and graphene by using titanium dioxide in the spinning solution of steps (1) and (2a), solves the problem of uneven local resistance, and enhances the conductivity of the substrate paper.

[0048] In addition, the present invention significantly improves the conductivity of the substrate paper by using graphene as an additive for the polyimide fiber in the spinning solution.

[0049] In addition, the method of the present invention solves the problem of uneven coating by using titanium dioxide in the coating liquid in steps (2b) and (3), and prevents problems such as uneven conductivity and decreased mechanical properties.

[0050] In addition, the present invention significantly increases the conductivity of the coating by using carbon nanotubes in the coating liquid, improves the surface adhesion between the polyamic acid and the substrate paper during coating, and improves the mechanical properties such as tensile strength.

[0051] The polyimide-based composite conductive paper of the present invention not only has good mechanical properties, conductive properties and conductive uniformity, but also has good high temperature resistance, and can be used in the fields of conduction, infrared emission, electromagnetic shielding, etc. BRIEF DESCRIPTION OF THE DRAWINGS

[0052] Figure 1 It is a schematic structural diagram of the composite conductive paper of the present invention.

[0053] Figure 2a It is a schematic structural diagram of the substrate paper of the present invention.

[0054] Figure 2b Schematic diagram of the structure of the coating of the present invention

[0055] Reference numerals

[0056] 10Base paper

[0057] 20 coatings

[0058] 30 coatings

[0059] 11Polyimide fiber

[0060] 12 Titanium dioxide

[0061] 13 Graphene

[0062] 21 Polyimide

[0063] 22 Titanium dioxide

[0064] 23 Graphene

[0065] 24 Carbon Nanotubes DETAILED DESCRIPTION

[0066] Hereinafter, the present invention will be described in detail with reference to the accompanying drawings.

[0067] Unless otherwise defined, all terms used herein, including technical or scientific terms, should be interpreted as having the same meaning as commonly understood by ordinary technicians in the field to which the present invention belongs. Therefore, unless explicitly defined, terms such as those defined in commonly used dictionaries should not be interpreted in an ideal or overly formal sense.

[0068] When the conditions and methods for measuring a property or parameter described in this specification are not described in detail, the property or parameter can be measured using the measurement conditions and methods generally used by those skilled in the art.

[0069] Unless otherwise specified, "%" used herein means % by weight.

[0070] 1. Method for preparing composite conductive paper

[0071] According to one aspect of the present invention, there is provided a method for preparing a composite conductive paper, the method comprising the following steps:

[0072] (1) dissolving a diamine in an organic solvent, then adding titanium dioxide and graphene and performing ultrasonic dispersion treatment, then adding dianhydride to perform polycondensation reaction, and then degassing to obtain a mixture containing polyamic acid, titanium dioxide and graphene, and

[0073] dividing the mixture into two parts: a first mixture as a spinning dope, and a second mixture for coating;

[0074] (2a) subjecting the first mixture to wet spinning, wet papermaking, drying and imidization treatment to obtain a polyimide-based composite fiber paper containing titanium dioxide and graphene, which is used as a substrate paper;

[0075] (2b) adding a solution containing an organic solvent and a dispersant to the second mixture obtained in step (1), followed by mixing to obtain a coating stock solution;

[0076] Then, adding carbon nanotubes to the coating stock solution and performing a dispersion treatment to obtain a coating solution containing polyamic acid, titanium dioxide, graphene and carbon nanotubes;

[0077] (3) The coating liquid is coated on both surfaces of the substrate paper obtained in step (2a), and subjected to thermal imidization treatment, and then pressed to obtain a composite conductive paper having a multilayer structure.

[0078] Each step is described in detail below.

[0079] Step (1) preparing a first mixture and a second mixture

[0080] First, a diamine is dissolved in an organic solvent, titanium dioxide and graphene are added, and ultrasonic dispersion treatment is performed, and then a dianhydride is added to perform polycondensation reaction, and then degassing is performed to obtain a mixture containing polyamic acid, titanium dioxide and graphene, and

[0081] The mixture was divided into two parts: a first mixture as a spinning dope, and a second mixture for coating.

[0082] There is no particular limitation on the diamine, and it can be a conventional diamine used in the art for preparing polyimide fibers. For example, the diamine can be one or more selected from 4,4'-diaminodiphenyl ether, 4,4'-diaminodiphenylmethane, 1,6-hexanediamine, triphenyl diether diamine, 2,5-bis(4-aminophenyl)pyrimidine, 5-amino-2-(4-aminophenyl)benzoxazole, and 4,4'-bis(4-aminophenoxy)biphenyl.

[0083] There is no particular limitation on the organic solvent, which can be a conventional organic solvent in the art, and is used to dissolve the diamine and the dianhydride, and react the diamine and the dianhydride therein to generate polyamic acid. For example, the organic solvent can be one or more selected from N,N'-dimethylformamide, N-methylpyrrolidone, N,N'-dimethylacetamide, and dimethyl sulfoxide.

[0084] There is no particular limitation on the dianhydride, which may be a dianhydride conventionally used in the art for preparing polyimide fibers. For example, the dianhydride may be one or more selected from 1,2,4,5-pyromellitic dianhydride, 3,3',4,4'-biphenyltetracarboxylic dianhydride, 3,3',4,4'-benzophenonetetracarboxylic dianhydride, 3,3',4,4'-diphenyl ethertetracarboxylic dianhydride, bisphenol A type diether dianhydride, and bisphenol F type diether dianhydride.

[0085] Titanium dioxide can be in the form of nano-powder, which can absorb opposite charges in liquid medium due to the surface charge. When the powders are close to each other, they repel each other due to the like charges, which is beneficial to the stability of the dispersion system. Therefore, titanium dioxide can be used to improve the dispersion stability of polyamic acid and graphene in the mixture.

[0086] In addition, titanium dioxide is preferably in the form of nano-scale powder with a large specific surface area to improve dispersibility and significantly increase the adhesion of the coating liquid prepared subsequently.

[0087] Graphene is a two-dimensional carbon nanomaterial with excellent electrical conductivity, thermal conductivity and mechanical properties. Graphene can be in powder form and is microscopically layered. As an additive material for polyimide fibers, it can improve the mechanical properties of the fiber, increase spinnability, and improve the electrical conductivity of the substrate paper. However, graphene is easily aggregated in liquid mixtures and is difficult to disperse. For this reason, the present invention improves the dispersibility of graphene by adding titanium dioxide.

[0088] Titanium dioxide and graphene can be added simultaneously. Alternatively, titanium dioxide can be added first and then graphene.

[0089] The ultrasonic dispersion treatment can be performed by conventional processes and equipment in the art, for example, by an ultrasonic nanomaterial disperser. Titanium dioxide and graphene can be uniformly dispersed in the mixture through the ultrasonic dispersion treatment.

[0090] The polycondensation reaction of diamine and dianhydride is a conventional reaction in the art, and polyamic acid can be obtained by the polycondensation reaction. There are no special restrictions on the time, pressure and temperature of the polycondensation reaction, and those skilled in the art can determine the appropriate time, pressure and temperature according to the diamine and dianhydride used. For example, when 4,4'-diaminodiphenyl ether is used as the diamine and 1,2,4,5-pyromellitic dianhydride is used as the dianhydride, the reaction can be carried out at normal pressure and a temperature of -5 to 35°C for 1.5 to 12.0 hours.

[0091] The molar ratio of diamine and dianhydride and their total addition amount can be determined according to the conventional technical knowledge in the art. For example, the molar ratio of diamine and dianhydride can be 1:0.95 to 1; preferably 1:1. In addition, the addition amount of the combination of diamine and dianhydride can be 8 to 15 parts by weight, preferably 9 to 13 parts by weight, relative to 100 parts by weight of the organic solvent.

[0092] The respective addition amounts of titanium dioxide and graphene can be determined by conventional technical means.

[0093] For example, relative to 100 parts by weight of the organic solvent, the amount of titanium dioxide added can be 0.5 to 6 parts by weight, preferably 1 to 5 parts by weight. If the amount of titanium dioxide added is too small, it will not improve the dispersibility and conductivity uniformity; if the amount of titanium dioxide added is too large, it may reduce the fiber strength, thereby affecting the strength of the final composite conductive paper.

[0094] Relative to 100 parts by weight of the organic solvent, the added amount of graphene can be 0.5 to 6 parts by weight, preferably 1 to 5 parts by weight. If the added amount of graphene is too small, the conductivity of the substrate paper is poor, the conductivity of the final composite conductive paper is reduced, and the resistance is uncontrollable; if the added amount of graphene is too large, it is easy to agglomerate and difficult to disperse, resulting in difficulties in spinning and coating, and reduced conductivity uniformity.

[0095] If the amount of organic solvent used is too small, the viscosity of the resulting mixture will be too high and spinning in the subsequent step (2a) will not be possible; if the amount of organic solvent used is too large, the spinnability of the first mixture will be poor in the subsequent process, causing the nascent fibers to break easily.

[0096] Degassing refers to removing bubbles from the mixture to prevent defects caused by bubbles during spinning or coating. Degassing can be performed by conventional processes, for example, standing degassing can be performed at room temperature (e.g., 20 to 25° C.). The degassing time can be 10 to 24 hours, preferably 12 to 22 hours, and most preferably 14 to 20 hours.

[0097] The obtained mixture is generally gray-green and is a suspension in which solid graphene and solid titanium dioxide are dispersed. The mixture can be divided into two parts: a first mixture as a spinning solution, and a second mixture for coating. Specifically, the first mixture is used to prepare a polyimide-based composite fiber paper as a substrate paper in step (2a), and the second mixture is used to prepare a coating solution in step (2b), and further to form a coating in step (3).

[0098] In one embodiment, a portion of the mixture can be selected as the first mixture (for example, 70 to 80 wt% relative to the total weight of the mixture) for use in step (2a), and the remaining mixture (for example, 30 to 20 wt% relative to the total weight of the mixture) can be selected as the second mixture for use in step (2b).

[0099] Step (2a) Preparation of substrate paper

[0100] The first mixture is subjected to wet spinning, wet papermaking, drying and imidization treatment to obtain polyimide-based composite fiber paper containing titanium dioxide and graphene, which is used as substrate paper.

[0101] Step (2a) can be carried out by conventional processes. For example, the wet spinning process can be found in CN102817096B, and the wet papermaking process can be found in CN102839560B. Fibers can be obtained by wet spinning, and then base paper can be obtained by wet papermaking.

[0102] The residual moisture in the base paper can be removed by drying. The drying temperature can be 50°C to 100°C, preferably 60°C to 95°C, and more preferably 70°C to 90°C. The drying time can be 5 min to 40 min, preferably 10 min to 30 min, and more preferably 15 min to 25 min.

[0103] By imidization, the polyamic acid in the paper can be converted into polyimide, thereby obtaining a polyimide-based composite fiber paper containing titanium dioxide and graphene. The imidization can be thermal imidization performed at a temperature of 200°C to 400°C.

[0104] Step (2b) Preparation of coating solution

[0105] Adding a solution containing an organic solvent and a dispersant to the second mixture obtained in step (1), followed by mixing, to obtain a coating stock solution;

[0106] Then, carbon nanotubes are added to the coating stock solution and dispersed to obtain a coating solution containing polyamic acid, titanium dioxide, graphene and carbon nanotubes.

[0107] The solution containing the organic solvent and the dispersant can be obtained by simply mixing the organic solvent and the dispersant.

[0108] The organic solvent is used to dilute the second mixture to enhance fluidity. The organic solvent may be the same as the organic solvent in step (1), for example, it may be one or more selected from N,N'-dimethylformamide, N-methylpyrrolidone, N,N'-dimethylacetamide, and dimethyl sulfoxide. Preferably, the organic solvent may be a combination of N,N'-dimethylacetamide and N-methylpyrrolidone, wherein the weight ratio of N,N'-dimethylacetamide to N-methylpyrrolidone is preferably 1:1.

[0109] The dispersant is used to disperse the carbon nanotubes, and the dispersant may be one or more selected from PEG-600, polystyrene, PEG-200, PEG-400, vinyl bisstearamide, and tristearic acid glyceryl.

[0110] The amount of the organic solvent added may be 80 to 120 parts, preferably 83 to 110 parts, and more preferably 85 to 105 parts, relative to 100 parts by weight of the second mixture.

[0111] The dispersant may be added in an amount of 0.1 to 5 parts, preferably 0.2 to 4 parts, and more preferably 0.3 to 3 parts, relative to 100 parts by weight of the second mixture.

[0112] The above components can be mixed by conventional processes such as sand milling, ball milling or three-roll milling to obtain a coating stock solution. Preferably, the mixing is carried out by sand milling. Thus, a coating stock solution in which each component is uniformly dispersed is obtained.

[0113] The carbon nanotubes may be single-walled carbon nanotubes or multi-walled carbon nanotubes, preferably single-walled carbon nanotubes with excellent electrical conductivity. The amount of carbon nanotubes added may be determined according to conventional technical knowledge in the art. For example, relative to 100 parts by weight of the coating stock solution, the amount of carbon nanotubes added may be 0.1 to 10 parts by weight, preferably 0.5 to 9 parts by weight, and most preferably 1 to 6 parts by weight.

[0114] By adding carbon nanotubes, the conductivity of the coating can be significantly enhanced. In addition, the surface bonding performance of polyamic acid and substrate paper during coating is improved, and the mechanical properties (such as tensile strength) are improved. In the coating liquid, the carbon nanotubes can be in a linear shape.

[0115] As mentioned above, carbon nanotubes are easy to aggregate and difficult to disperse. Therefore, the present invention particularly uses titanium dioxide to improve its dispersibility.

[0116] The coating liquid containing polyamic acid, titanium dioxide, graphene and carbon nanotubes can be obtained by dispersing the polyamic acid, titanium dioxide, graphene and carbon nanotubes through conventional processes such as sand milling, ball milling or triple roll milling.

[0117] In addition, there is no particular limitation on the order in which steps (2a) and (2b) are performed. For example, step (2a) may be performed first, and then step (2b). Alternatively, step (2b) may be performed first, and then step (2a). Alternatively, steps (2a) and (2b) may be performed separately at the same time.

[0118] Step (3) Preparation of composite conductive paper

[0119] The coating liquid is coated on both surfaces of the substrate paper obtained in step (2a), and subjected to thermal imidization treatment, and then pressed to obtain a composite conductive paper with a multilayer structure.

[0120] The coating can be carried out by conventional processes in the art, for example, a scraper can be used for coating. Double-sided coating can be carried out multiple times as needed, for example, 2 times, 3 times or more times, to form a thicker coating and obtain a better conductive effect.

[0121] The coating liquids coated on the two surfaces may be equal in amount (ie, equal in weight or volume) to each other, so that the two coatings obtained on the two surfaces have equal thicknesses, thereby making the two surfaces of the composite conductive paper have the same properties.

[0122] The coating amount of the coating liquid can be determined according to conventional techniques in the art. The coating amount refers to the total coating amount on both surfaces of the substrate paper. Generally, the coating amount can be 5 to 100 g / m 2 , preferably 10 to 60 g / m 2 , more preferably 13 to 50 g / m 2 The coating amount can affect the conductive properties of the composite conductive paper. Too little coating amount may lead to uneven conductivity and too high surface resistance; while too much coating amount may reduce the adhesion of the coating layer, making it prone to cracking and delamination; in addition, if the resulting paper is too thick, its flexibility will be affected.

[0123] By coating, the carbon nanotubes can be evenly distributed on the surface of the substrate paper, so that they can not only conduct electricity themselves, but also connect to graphene to enhance its conductive properties.

[0124] Thermal imidization can be carried out by conventional processes in the art. For example, the temperature of thermal imidization can be 200 to 350° C., preferably 250 to 340° C., and more preferably 300 to 320° C. Through thermal imidization, the polyamic acid in the coating liquid can be converted into polyimide, and the organic solvent in the coating liquid can be removed at the same time.

[0125] The pressing may be performed by conventional techniques in the art, and for example, the pressing may include soft roll pressing and hard roll pressing.

[0126] The temperature of the soft rolling press can be 50-200° C., and the pressure can be 0.1-2 MPa; preferably, the temperature is 60-150° C., and the pressure is 0.2-1.5 MPa; more preferably, the temperature is 80-120° C., and the pressure is 0.3-1.2 MPa.

[0127] Through soft roller pressing, the paper can be calendered and softened as a whole, so that the paper surface is brighter and smoother, and the uniformity of the paper is improved.

[0128] The temperature of the hard rolling can be 100-350° C., and the pressure can be 0.1-3 MPa; preferably, the temperature is 150-330° C., and the pressure is 0.2-2 MPa; more preferably, the temperature is 200-320° C., and the pressure is 0.3-1.5 MPa.

[0129] The conductivity of paper can be improved by hard rolling. The principle is that hard rolling will make the paper thinner, the paper will be more tightly bound inside, and the contact area of ​​conductive graphene, titanium dioxide and carbon nanotubes will be larger, thus improving the conductivity.

[0130] In addition, since hard rolling is performed at a high temperature, the polyamic acid that is not completely imidized in the paper can also be imidized, thereby improving the strength of the paper.

[0131] The obtained composite conductive paper has a multi-layer structure, as described in detail below.

[0132] 2. Composite conductive paper

[0133] According to another aspect, the present invention provides a composite conductive paper, which can be prepared by the above method. In the composite conductive paper, a coating is respectively provided on both surfaces of a substrate paper, the substrate paper comprises polyimide fiber, titanium dioxide and graphene, and the coating comprises polyimide, titanium dioxide, graphene and carbon nanotubes.

[0134] like Figure 1 As shown, the composite conductive paper of the present invention comprises a substrate paper 10 and a coating layer 20 and a coating layer 30 respectively on two opposite surfaces of the substrate paper. The coating layer 20 and the coating layer 30 have the same structure, composition and thickness. That is, the coating layer 20 and the coating layer 30 are identical, thereby ensuring the same performance.

[0135] The substrate paper 10 is a polyimide-based composite fiber paper, and its thickness can generally be 0.07-0.09 mm.

[0136] like Figure 2a As shown, in the substrate paper 10, the polyimide fibers 11 form a three-dimensional network, in which the particulate titanium dioxide 12 and the layered graphene 13 are uniformly distributed, so that the substrate paper has conductivity and maintains the high temperature resistance and mechanical properties of the substrate paper.

[0137] The coatings 20 and 30 are polyimide-based coatings, and the total thickness of the coatings 20 and 30 may generally be 0.02 to 0.06 mm.

[0138] like Figure 2b As shown, in the coating 20, polyimide 21 is a continuous phase, constituting the main body of the coating, in which titanium dioxide 22, graphene 23 and carbon nanotubes 24 are uniformly distributed. Specifically, titanium dioxide is distributed in a granular form; graphene has a layered structure and is laid flat in the entire planar coating constructed by polyimide; carbon nanotubes are linear, randomly distributed in the entire coating, intersecting each other and connecting graphene. As a result, the obtained coating 20 has excellent and uniform conductive properties.

[0139] The composite conductive paper of the present invention has good mechanical properties (such as tensile strength). In one embodiment, the tensile strength of the composite conductive paper can be 3.0-4.0 KN / m in the transverse direction and 3.8-4.8 KN / m in the longitudinal direction. The detection method can refer to GB / T12914-2008.

[0140] In addition, the composite conductive paper of the present invention has good conductive performance and conductive uniformity. Moreover, by adjusting the amount of titanium dioxide, graphene and carbon nanotubes added to the coating and adjusting the coating thickness, the resistance of the composite conductive paper of the present invention can be easily changed within a certain range, thereby meeting the needs of different fields.

[0141] Moreover, the composite conductive paper of the present invention has long-term high temperature resistance. For example, the composite conductive paper of the present invention can still maintain good mechanical properties, conductive properties and conductive uniformity after being used for more than 200 hours, such as 250 to 300 hours, at a temperature of 200°C or above, such as 200°C to 300°C.

[0142] Example

[0143] Hereinafter, the present invention will be described in detail with reference to embodiments to specifically describe the present invention. However, embodiments of the present invention may be modified into various other forms, and the scope of the present invention should not be construed as being limited to the embodiments described below. Embodiments of the present invention are provided to more fully describe the present invention to those of ordinary skill in the art.

[0144] The experimental methods in the following examples, unless otherwise specified, are generally conventional conditions in the art or conditions recommended by the manufacturer; the raw materials and equipment used are all commercially available from conventional markets, etc., unless otherwise specified.

[0145] Example 1 Preparation of composite conductive paper

[0146] The polyimide-based composite conductive paper is prepared according to the following method, the method comprising:

[0147] Step (1): 1000 g of 4,4'-diaminodiphenyl ether as a diamine is dissolved in 20000 g of a mixed solvent of N,N'-dimethylacetamide and N-methylpyrrolidone (weight ratio of 1:1) as an organic solvent, and stirred until dissolved.

[0148] 400 g of titanium dioxide powder (powder size is 20 nm) and 400 g of graphene powder (powder size is 2 μm) were added simultaneously under stirring conditions, and ultrasonic (ultrasonic power is 130 w) dispersion was performed for 60 min to uniformly disperse the titanium dioxide powder and graphene powder. The amount of titanium dioxide added was 2 parts by weight and the amount of graphene added was 2 parts by weight relative to 100 parts by weight of the organic solvent.

[0149] Then, 1089 g of 1,2,4,5-pyromellitic dianhydride as dianhydride was added (the molar ratio of diamine to dianhydride was 1:1, and the added amount of the combination of diamine and dianhydride was 10.5 parts by weight relative to 100 parts by weight of the organic solvent), and stirred for 4 hours to perform a condensation reaction to produce polyamic acid.

[0150] Next, the mixture was allowed to stand at room temperature (20° C.) for degassing for about 16 hours to obtain a mixture containing polyamic acid, titanium dioxide and graphene.

[0151] Then, the mixture was divided into two parts: 75 wt% of the first mixture as spinning dope (17167 g), and 25 wt% of the second mixture for coating (5722 g).

[0152] Step (2a): The first mixture (17167 g) is wet-spun through a spinning machine (Handan Hongda Chemical Fiber Machinery Co., Ltd., KT / HD3190GQ), and wet-papered through a 500 / 30 fiber fabric machine production line (Liaocheng Huasen Machinery Co., Ltd., 500 / 30) to produce base paper.

[0153] Next, the paper was dried at 80° C. for 20 min and then thermally imidized at 350° C. to prepare a polyimide-based composite fiber paper containing titanium dioxide and graphene, which was used as a substrate paper.

[0154] Step (2b): Add a solution (5500 g) consisting of 5000 g of a mixed solvent and 50 g of a dispersant PEG-600 to the second mixture (5722 g) obtained in step (1), wherein the mixed solvent consists of N,N'-dimethylacetamide and N-methylpyrrolidone (weight ratio is 1:1), and then mix by sand milling (sand mill speed is 3000 rpm) to obtain a coating stock solution. Wherein, relative to 100 parts by weight of the second mixture, the amount of the organic solvent added is 87.4 parts by weight, and the amount of the dispersant added is 0.87 parts by weight.

[0155] Then, 200 g of single-walled carbon nanotubes were added to the coating solution (i.e., the amount of carbon nanotubes added was 1.9 parts by weight relative to 100 parts by weight of the coating solution), and the solution was dispersed by sand milling for 120 minutes to obtain a coating solution containing polyamic acid, titanium dioxide, graphene and carbon nanotubes.

[0156] Step (3): Using a scraper, evenly apply the coating liquid prepared in step (2b) on both surfaces of the substrate paper obtained in step (2a) in equal amounts, with the total coating amount on both surfaces being 30 g / m 2 , and then thermal imidization treatment at 300 °C for 30 min.

[0157] Next, the resultant was soft-rolled at 100° C. and 0.4 MPa, and then hard-rolled at 310° C. and 0.8 MPa, thereby obtaining a composite conductive paper having a multilayer structure. The thickness of the composite conductive paper was 0.12 mm.

[0158] Example 2a (Changing the Types of Diamine and Dianhydride in Step (1))

[0159] The same steps as in Example 1 were performed except that the diamine in step (1) was changed to 1000 g of 4,4'-diaminodiphenylmethane and the dianhydride was changed to 1484 g of 3,3',4,4'-biphenyltetracarboxylic dianhydride (the molar ratio of diamine to dianhydride was still 1:1) to obtain a polyimide-based composite conductive paper.

[0160] Example 2b (Changing the Types of Diamine and Dianhydride in Step (1))

[0161] The same steps as in Example 1 were performed except that the diamine in step (1) was changed to 1000 g of triphenyl diether diamine and the dianhydride was changed to 1497 g of 3,3',4,4'-biphenyltetracarboxylic dianhydride (the molar ratio of diamine to dianhydride was still 1:1) to obtain a polyimide-based composite conductive paper.

[0162] Comparative Example 1 (Omitting titanium dioxide in step (1))

[0163] The same steps as in Example 1 were performed except that titanium dioxide powder was not added in step (1) to obtain a polyimide-based composite conductive paper.

[0164] Comparative Example 2 (Omitting graphene in step (1))

[0165] The same steps as in Example 1 were performed except that no graphene powder was added in step (1) to obtain a polyimide-based composite conductive paper.

[0166] Comparative Example 3 (Omitting the carbon nanotubes in step (2b))

[0167] The same steps as in Example 1 were performed except that no carbon nanotubes were used in step (2b), thereby obtaining a polyimide-based composite conductive paper.

[0168] Comparative Example 4a (replacing the titanium dioxide powder in step (1) with silver powder)

[0169] The same steps as in Example 1 were performed except that the titanium dioxide powder in step (1) was replaced by the same weight of silver powder to obtain a polyimide-based composite conductive paper.

[0170] Comparative Example 4b (replacing titanium dioxide in the second mixture with silver powder)

[0171] Except for the following steps, the same steps as those in Example 1 were carried out to obtain a polyimide-based composite conductive paper.

[0172] The first mixture remains unchanged. In addition, a new second mixture is prepared in step (1) to replace the original second mixture, wherein the titanium dioxide powder in step (1) is replaced by the same weight of silver powder. The obtained new second mixture is used in step (2b) to obtain a coating solution containing polyamic acid, graphene, silver powder and carbon nanotubes.

[0173] Comparative Example 4c (changing the first mixture to prepare pure polyimide substrate paper, and replacing the titanium dioxide in the second mixture with silver powder)

[0174] Except for the following steps, the same steps as those in Example 1 were carried out to obtain a polyimide-based composite conductive paper.

[0175] In step (1), a new first mixture is prepared in which titanium dioxide and graphene are omitted. The obtained first mixture is used in step (2a) to obtain a polyimide substrate paper without titanium dioxide and graphene.

[0176] In addition, a new second mixture is prepared in step (1), wherein the titanium dioxide powder is replaced by the same weight of silver powder. The obtained second mixture is used in step (2b) to obtain a coating solution containing polyamic acid, graphene, silver powder and carbon nanotubes.

[0177] Experimental example

[0178] Experimental Example 1 Tensile Strength Measurement

[0179] The composite conductive papers prepared in Examples 1 to 2 and Comparative Examples 1 to 4 were cut into strips with a length of 150 mm and a width of 15 mm. Then, according to GB / T12914-2008, the tensile strength of the strips was measured using a computer-controlled tensile strength tester (Shandong Derui Instrument Co., Ltd., model DRK101) at a temperature of 23° C. and a relative humidity of 50% RH.

[0180] The results are shown in Table 1 below.

[0181] Table 1

[0182]

[0183] From Table 1, we can see that

[0184] Compared with Example 1, the tensile strength of the composite conductive papers of Examples 2a and 2b did not change significantly.

[0185] Compared with Example 1,

[0186] In Comparative Example 1, titanium dioxide is omitted, which makes it difficult to evenly disperse the spinning solution and the coating solution, resulting in a significant decrease in the uniformity of the composite conductive paper, thereby greatly reducing the tensile strength.

[0187] In Comparative Example 2, graphene is omitted, resulting in a decrease in the tensile strength of the composite conductive paper.

[0188] In Comparative Example 3, carbon nanotubes were omitted, and the tensile strength of the composite conductive paper was significantly reduced.

[0189] Compared with Example 1,

[0190] In Comparative Example 4a, silver powder is used instead of titanium dioxide powder, which makes it difficult to evenly disperse the spinning solution and the coating solution, thereby reducing the tensile strength of the composite conductive paper.

[0191] In Comparative Example 4b, silver powder is used in the coating solution instead of titanium dioxide powder. The substrate paper is not changed, which only reduces the dispersibility of the conductive material in the coating and has no significant effect on the tensile strength of the composite conductive paper.

[0192] In Comparative Example 4c, the substrate paper does not contain titanium dioxide and graphene and the titanium dioxide in the coating solution is replaced by silver powder, resulting in a slight decrease in tensile strength. This shows that omitting titanium dioxide and graphene will reduce the tensile strength of the composite conductive paper.

[0193] Experimental Example 2: Tensile Strength Retention after Long-term High-temperature Heating

[0194] The experiment was conducted under the conditions of Experimental Example 1 except that the specimens were heated in an oven at 280° C. for 200 h.

[0195] The results are shown in Table 2 below.

[0196] Table 2

[0197]

[0198] As can be seen from Table 2, since the base material of the composite conductive paper in Examples 1 to 2 and Comparative Examples 1 to 4 is polyimide, which has excellent high temperature resistance, and the various additives also have excellent temperature resistance, after being heated at a high temperature (280° C.) for 200 hours, the tensile strength retention rate of the composite conductive paper can reach more than 90%.

[0199] Experimental Example 3 Resistance Measurement at Room Temperature (23°C)

[0200] The polyimide-based composite conductive papers prepared in Examples 1 to 2 and Comparative Examples 1 to 4 were cut into samples of standard A4 paper size (210 mm × 297 mm), and then a small sample of 50 × 50 mm was cut from the four corners and the middle of each paper, resulting in a total of 5 small samples.

[0201] Next, a high-temperature four-probe resistivity test system (Ningbo Ruike Micro Intelligent Technology Co., Ltd., model FT-351A) was used to measure the resistance of the small sample at a temperature of 23°C using a four-probe dual-electric combined measurement method.

[0202] The obtained resistances were averaged and the results are shown in Table 3 below.

[0203] Table 3

[0204] Resistance (Ω / □) Example 1 20 Example 2a 22 Example 2b 21 Comparative Example 1 436 Comparative Example 2 572 Comparative Example 3 605 Comparative Example 4a 427 Comparative Example 4b 184 Comparative Example 4c 376

[0205] It can be seen from Table 3 that, compared with Example 1, the resistance of the composite conductive paper of Examples 2a and 2b does not change much.

[0206] Compared with Example 1,

[0207] In Comparative Example 1, titanium dioxide is omitted, resulting in a significant decrease in electrical conductivity and a significant increase in resistance.

[0208] In Comparative Example 2a, graphene is omitted, the conductive performance is significantly reduced, and the resistance is significantly increased.

[0209] In Comparative Example 3, carbon nanotubes were omitted, and the conductivity dropped sharply and the resistance increased significantly.

[0210] Compared with Example 1,

[0211] In Comparative Example 4a, the titanium dioxide powder in step (1) is replaced with silver powder. Although silver powder has good conductivity, it is not dispersible, which greatly reduces the conductivity of the composite conductive paper and greatly increases the resistance.

[0212] In Comparative Example 4b, silver powder was used in the coating solution instead of titanium dioxide powder, and the substrate paper was not changed. This also caused the conductive performance of the composite conductive paper to drop significantly, and the resistance to increase significantly.

[0213] In Comparative Example 4c, the substrate paper does not contain titanium dioxide and graphene, and the titanium dioxide powder in the coating solution is replaced with silver powder, which also greatly reduces the dispersibility and conductivity, and greatly increases the resistance.

[0214] Experimental Example 4 Resistance Measurement at High Temperature (280°C)

[0215] For the composite conductive papers of Examples 1 to 2 and Comparative Examples 1 to 4, the experiment was conducted according to the conditions of Experimental Example 3 except that the resistance was measured at a temperature of 280°C.

[0216] The results are shown in Table 4 below.

[0217] Table 4

[0218] Resistance (Ω / □) Example 1 21 Example 2a 22 Example 2b 23 Comparative Example 1 428 Comparative Example 2 585 Comparative Example 3 600 Comparative Example 4a 422 Comparative Example 4b 180 Comparative Example 4c 380

[0219] It can be seen from Table 4 that, because the polyimide used as the base material has good high temperature stability and the various additives in the system are all high heat-resistant materials, high temperature has no effect on the conductive properties of the composite conductive paper.

[0220] Experimental Example 5 Resistance Uniformity Measurement

[0221] For the composite conductive papers of Examples 1 to 2 and Comparative Examples 1 to 4, experiments were conducted according to the conditions of Experimental Example 3, and the resistances of 5 small samples were recorded respectively, and the standard deviation was calculated to determine the resistance uniformity. The results are shown in Table 5 below.

[0222] The calculation formula of the standard deviation is as follows:

[0223]

[0224] Among them, xi represents the value of each sample,

[0225] x represents the mean of all samples.

[0226] n represents the number of samples.

[0227] Table 5

[0228] Resistance standard deviation of 5 small samples Example 1 1.6 Example 2a 1.0 Example 2b 1.2 Comparative Example 1 446.3 Comparative Example 2 10.2 Comparative Example 3 1.1 Comparative Example 4a 375.3 Comparative Example 4b 60.9 Comparative Example 4c 242.1

[0229] It can be seen from Table 5 that, compared with Example 1, the change in the types of diamine and dianhydride in Examples 2a and 2b has no significant effect on the resistance uniformity of the composite conductive paper.

[0230] Compared with Example 1,

[0231] In Comparative Example 1, titanium dioxide was omitted, and the resistance uniformity was significantly poor.

[0232] In Comparative Example 2, graphene is omitted, which is beneficial to dispersibility, resulting in excellent resistance uniformity.

[0233] In Comparative Example 3, the carbon nanotubes are omitted, which is beneficial to dispersibility and makes the resistance uniformity excellent.

[0234] Compared with Example 1,

[0235] In Comparative Example 4a, the titanium dioxide powder in step (1) was replaced with silver powder, and the resistance uniformity was significantly deteriorated.

[0236] In Comparative Example 4b, silver powder was used in the coating solution instead of titanium dioxide powder, and the substrate paper was not changed, but the resistance uniformity was significantly deteriorated.

[0237] In Comparative Example 4c, the substrate paper does not contain titanium dioxide and graphene, and the titanium dioxide in the coating solution is replaced by silver powder, and the resistance uniformity is significantly deteriorated.

[0238] It can be seen from the above experimental examples that the present invention obtains a composite conductive paper having excellent mechanical properties, conductive properties, conductive uniformity and long-term high temperature resistance by using substrate paper and coating with specific compositions.

[0239] Although the preferred embodiments of the present invention have been disclosed for illustrative purposes, those skilled in the art will appreciate that various modifications, additions and substitutions are possible, without departing from the scope and spirit of the invention as disclosed in the accompanying claims.

Claims

1. A method for preparing a composite conductive paper, the method comprising the following steps: (1) dissolving a diamine in an organic solvent, then adding titanium dioxide and graphene and performing ultrasonic dispersion treatment, then adding dianhydride to perform polycondensation reaction, and then degassing to obtain a mixture containing polyamic acid, titanium dioxide and graphene, and dividing the mixture into two parts: a first mixture as a spinning dope, and a second mixture for coating; (2a) subjecting the first mixture to wet spinning, wet papermaking, drying and imidization treatment to obtain a polyimide-based composite fiber paper containing titanium dioxide and graphene, which is used as a substrate paper; (2b) adding a solution containing an organic solvent and a dispersant to the second mixture obtained in step (1), followed by mixing to obtain a coating stock solution; Then, adding carbon nanotubes to the coating stock solution and performing a dispersion treatment to obtain a coating solution containing polyamic acid, titanium dioxide, graphene and carbon nanotubes; (3) The coating liquid is coated on both surfaces of the substrate paper obtained in step (2a), and subjected to thermal imidization treatment, and then pressed to obtain a composite conductive paper having a multilayer structure.

2. The method according to claim 1, wherein: In the step (1), The diamine is one or more selected from 4,4'-diaminodiphenyl ether, 4,4'-diaminodiphenylmethane, 1,6-hexanediamine, triphenyl diether diamine, 2,5-bis(4-aminophenyl)pyrimidine, 5-amino-2-(4-aminophenyl)benzoxazole, and 4,4'-bis(4-aminophenoxy)biphenyl, The organic solvent is one or more selected from N,N'-dimethylacetamide, N-methylpyrrolidone, N,N'-dimethylformamide, and dimethyl sulfoxide. The dianhydride is one or more selected from 1,2,4,5-pyromellitic dianhydride, 3,3',4,4'-biphenyltetracarboxylic dianhydride, 3,3',4,4'-benzophenonetetracarboxylic dianhydride, 3,3',4,4'-diphenyl ether tetracarboxylic dianhydride, bisphenol A type diether dianhydride, bisphenol F type diether dianhydride, The molar ratio of the diamine to the dianhydride is 1:0.95-1; The added amount of the combination of the diamine and the dianhydride is 8 to 15 parts by weight relative to 100 parts by weight of the organic solvent; The amount of titanium dioxide added is 0.5 to 6 parts by weight relative to 100 parts by weight of the organic solvent. The added amount of the graphene is 0.5 to 6 parts by weight relative to 100 parts by weight of the organic solvent; The weight ratio of the first mixture to the second mixture is 70-80:30-20.

3. The method according to claim 1, wherein: In the step (2a), The drying temperature is 50℃~100℃, and the drying time is 5min~40min. The imidization is thermal imidization performed at a temperature of 200°C to 400°C.

4. The method according to claim 1, wherein: In the step (2b), The organic solvent is one or more selected from N,N'-dimethylformamide, N-methylpyrrolidone, N,N'-dimethylacetamide, and dimethyl sulfoxide. The dispersant is one or more selected from PEG-600, polystyrene, PEG-200, PEG-400, vinyl bisstearamide, and tristearic acid glyceryl. wherein the organic solvent is added in an amount of 80 to 120 parts by weight, and the dispersant is added in an amount of 0.1 to 5 parts by weight relative to 100 parts by weight of the second mixture; The amount of the carbon nanotubes added is 0.1 to 10 parts by weight relative to 100 parts by weight of the coating stock solution.

5. The method according to claim 1, wherein: In the step (3), The coating amount of the coating liquid is 5 to 100 g / m 2 , The temperature of the thermal imidization treatment is 200-350°C. The pressing includes soft roller pressing and hard roller pressing. The temperature of the soft rolling is 50-200°C and the pressure is 0.1-2MPa. The temperature of the hard rolling is 100-350° C., and the pressure is 0.1-3 MPa.

6. A composite conductive paper, prepared by the method of claim 1, wherein each of the two surfaces of the substrate paper has a coating layer, The substrate paper comprises polyimide fiber, titanium dioxide and graphene, The coating comprises polyimide, titanium dioxide, graphene and carbon nanotubes.

Citation Information

Patent Citations

  • Continuous production method of polyimide fibers

    CN102817096B

  • Preparation method of polyimide fiber paper

    CN102839560B